Influence of the relative humidity to the damage detection effectiveness of an ITO/PMMA nanocomposite film sensor - Takiuti, Breno Ebinuma [UNESP]; Lopes, Vicente [UNESP]; Brennan, Michael J. [UNESP]; Orlandi, Marcelo Ornaghi [UNESP] (My University, 2015)
One of the main applications of structural health monitoring (SHM) is damage detection in aerospace structures. Several techniques have been studied in order to efficiently detect, locate and measure the size of the damage based on impedance measurements or the guided wave approach. This work uses a novel SHM method based on a nanocomposite film sensor, which can be applied to the monitored structure in the form of a film coating and the damage can be detected by monitoring the resistance variations of the coating. The nanocomposite sensor was produced by combining ITO (Indium Tin Oxide) nanowires into a PMMA (Poly(methyl methacrylate)) matrix, forming a translucent film with several nanowires which form conductive paths. By placing several measurement terminals throughout this film sensor, it is possible to detect the damage, and in some conditions to locate the damage. It is known that some measurements used for SHM such as impedance measurements are influenced by environmental changes, such as temperature and humidity. In order to have a better understanding of the proposed nanocomposite sensor, several tests were made using an environmental chamber, maintaining the temperature at a constant level and varying the humidity. For damage location, several measurements were taken at different positions, in order to compare the resistance of various paths. Initial measurements of the resistances varied from 1 to 12 kΩ, which is an acceptable range for this application. Humidity tests showed that, in general, with low humidity (values lower than 70%), the resistance did not result in significant variations, however with higher humidity levels (higher than 70%) the resistances started to decrease with the increase of the humidity. The results showed that the approach is promising, although it still needs some development.